2017
DOI: 10.1002/anie.201707819
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo X‐ray Imaging of Transport of Renal Clearable Gold Nanoparticles in the Kidneys

Abstract: With more and more engineered nanoparticles (NPs) being designed renal clearable for clinical translation, fundamental understandings of their transport in the different compartments of kidneys become increasingly important. Here, we report noninvasive X-ray imaging of renal clearable gold NPs (AuNPs) in normal and nephropathic kidneys. By quantifying the transport kinetics of the AuNPs in cortex, medulla and pelvis of the normal and injured kidneys, we found that ureteral obstruction not just blocked the NP e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 30 publications
1
74
0
Order By: Relevance
“…The clearance kinetics of GS‐AuNPs in different compartments of the kidney can be noninvasively quantified with X‐ray imaging . Owing to high X‐ray attenuation of gold atoms, GS‐AuNPs were clearly observed in the renal cortex, medulla, and pelvis of the kidneys at 2 min p.i.…”
Section: Interactions With Tissues and Organsmentioning
confidence: 99%
“…The clearance kinetics of GS‐AuNPs in different compartments of the kidney can be noninvasively quantified with X‐ray imaging . Owing to high X‐ray attenuation of gold atoms, GS‐AuNPs were clearly observed in the renal cortex, medulla, and pelvis of the kidneys at 2 min p.i.…”
Section: Interactions With Tissues and Organsmentioning
confidence: 99%
“…This important concept was supported by Zheng and co-workers by using renal clearable gold nanoparticles that extravasated into the tumor bed and penetrated into various tumors in animal models through the small molecular EPR effect. [55,56] …”
Section: Contrast Agents For Optical Imagingmentioning
confidence: 99%
“…[3] Using ultrasmall AuNPs as am odel, our group has also advanced the fundamental understanding of nephrology on the nanoscale by developing ac lass of renalclearable AuNPs and discovered an inverse size-scaling law in glomerular filtration of engineered nanoparticles in the sub-nm regime,w hich opens up new pathways to evaluating kidney dysfunctions. In the past years,i nvivo fluorescence imaging, [5] positron emission tomography (PET), [6] and single photon emission computed tomography (SPECT) [7] have been adopted to unravel kidney clearance kinetics of AuNPs,b ut these techniques did not offer anatomic information as well as clearance kinetics in different kidney compartments.M eanwhile,p lanar X-ray imaging [8] and computed tomography (CT) [9] can provide anatomic information of AuNP clearance,b ut the temporal resolution is relatively low,making it hard to directly visualize nanoparticle transport coupled with the blood flow dynamics. In the past years,i nvivo fluorescence imaging, [5] positron emission tomography (PET), [6] and single photon emission computed tomography (SPECT) [7] have been adopted to unravel kidney clearance kinetics of AuNPs,b ut these techniques did not offer anatomic information as well as clearance kinetics in different kidney compartments.M eanwhile,p lanar X-ray imaging [8] and computed tomography (CT) [9] can provide anatomic information of AuNP clearance,b ut the temporal resolution is relatively low,making it hard to directly visualize nanoparticle transport coupled with the blood flow dynamics.…”
mentioning
confidence: 99%
“…Thed erived fvv of left UUO kidneys was approximately 65 %l ower than that of contralateral right kidneys (3.3 AE 0.95 %v s. 9.3 AE 1.9 %f or left UUO and right kidneys, respectively,F igure 3E and Supporting Information, Figure S10), which was consistent with the results from previous studies [20] measuring renal arterial blood flow that found acute reduction (greater than 50 %) of renal blood perfusion in UUO kidneys.G FR values deduced from the slopes showed that the left UUO kidneys (0.26 AE 0.02 mL min À1 mL À1 )h ad only approximately 45 %ofthe GFR of the contralateral right kidneys (0.57 AE 0.04 mL min À1 mL À1 ) (Figure 3Fand Supporting Information, Figure S9), which was slightly higher than the GFR values measured previously for UUO kidneys (5- 25 %t hat of the contralateral kidneys) through the bilateral ureter catheterization method. [20c,21] This discrepancym ay result from our recently reported fact that the transport of probes in different segments (cortex-to-medulla-to-pelvis)o f the UUO kidney was significantly slowed down, together with increased renal cellular uptake compared to that of the contralateral, unobstructed kidney, [8] rendering ureter catheterization atechnique that tends to underestimate the GFR of UUO kidneys.…”
mentioning
confidence: 99%